What Matters for Urban Adolescents' Engagement and Disengagement in School: A Mixed-Methods Study. Issue 5 (September 2019) - Fredricks, Jennifer A.; Parr, Alyssa K.; Amemiya, Jamie L.; Wang, Ming-Te; Brauer, Scott
This study uses a mixed-method sequential exploratory design to examine influences on urban adolescents' engagement and disengagement in school. First, we interviewed 22 middle and high school students who varied in their level of engagement and disengagement. Support from adults and peers, opportunities to make choices, and external incentives aligned with greater engagement. In contrast, a strict disciplinary structure, an irrelevant and boring curriculum, disengaged peers, and lack of respect by adults coincided with greater disengagement. From these interviews, we tested whether these factors were statistically significant predictors of engagement and disengagement in a sample of 611 middle and high school students. In the majority of models, these predictors were significantly related to engagement and disengagement in the expected direction. Implications of findings for educational practice are discussed.